ARTIFICIAL INTELLIGENCE IN MANGROVE MANAGEMENT POLICY IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Sepnina Like Lestari; Henky Mayaguezz; Indra Gumay Febryano (Universitas Mataram, 2025)
Mangroves play a crucial role in climate change mitigation and coastal protection, yet they face pressures from environmental degradation and limited policy implementation. This study employs a systematic literature review to examine the role of artificial intelligence (AI) in mangrove management and its policy implications in Indonesia. Findings indicate that AI, through machine learning, deep learning, and integration with remote sensing data, is effective in monitoring, mapping, restoration assessment, and predicting ecosystem changes. These technologies have the potential to support evidence-based policymaking, including prioritizing restoration areas, optimizing resource allocation, and enhancing decision-making systems. However, AI adoption faces challenges related to data quality and availability, institutional capacity, and ethical and governance concerns. The study highlights opportunities for developing inclusive and interdisciplinary AI governance frameworks, which could strengthen policy effectiveness and promote sustainable mangrove management in Indonesia.